Case report: Functional characterization of a novel CHD7 intronic variant in patients with CHARGE syndrome - Rossi, Cesare; Ramadan, Sherin; Evangelisti, Cecilia; Ferrari, Simona; Accadia, Maria; Toydemir, Reha M.; Panza, Emanuele (Frontiers in Genetics, 2023)
Background. CHARGE syndrome is characterized by high clinical variability; hence molecular confirmation of the clinical diagnosis is of pivotal importance. Most patients have a pathogenic variant in CHD7 gene; however, these variants are distributed throughout the gene and most of the cases are due to de novo mutations. Often, assessing the pathogenetic effect of a variant can be challenging, requiring the design of a unique experiment for each specific case. Method. Here we describe a new CHD7 intronic variant, c.5607+17A>G, identified in two unrelated patients. An in-depth molecular characterization of this variant was performed, using exon trapping vectors to construct minigenes. Results. This approach pinpoints the pathogenetic effect of the variant on CHD7 gene splicing, which was subsequently confirmed on cDNA synthetized from patient’s lymphocytes RNA. Our results were further corroborated by the introduction of other substitutions at the same nucleotide position showing that the c.5607+17A>G specifically alters splicing possibly due to the generation of a recognition motif for the recruitment of a splicing effector. Conclusion. Here we identify a novel pathogenetic variant affecting splicing, and we provide a detailed molecular characterization and a possible functional explanation.